Pencegahan Kecurangan oleh Bawaslu pada Pemungutan Suara Pemilu - Andri Pramana; Ainur Ropik; Erik Darmawan (Jurnal Prodi Ilmu Politik, 2023)
ABSTRACT This research discusses the Prevention of Cheating by Bawaslu in the Re-Voting of the PSU Pilkada of Pali regency in 2020.The purpose of this study is to find out the implementation of Prevention of Cheating by Bawaslu in the Re-Voting of the PSU Pilkada of Pali Regency and tofind out thein habiting and support ingfactors of Bawaslu incarry ing out Fraud Prevention in the PSU Pilkada of Pali Regency in 2020. The object in this research is the Pali Regency Bawaslu. The theory used is Election Theory toanalyze the Prevention of Cheating by Bawaslu at PSU in Pali Regency.The method used in this research is descriptive qualitative method. The source of data inthis research is the Coordinator of the Division for Handling and Violations of Election Disputes and the Community. Data is collected and analyzed through documentation and interviews. There sultsofth is study Bawaslu have prevented fraud in the implementation of PSU by changing KPPS officers, re-collecting data on the final voterlistor DPT, advising against money politics, calling not toabstain fromvoting, aswellasby in habiting factors, lack of public cawareness, limited time for holding PSU, lack of Human resources, human resources and supported by the Central, Provinci al Bawaslu and the Gakkumdu Center consisting of the Police, Attorney General's Office and Bawaslu. Keywords: prevention of fraud. Bawaslu Pali district, PSU